Osseointegrated implants into a variety of composite free flaps: A comparative analysis. Issue 3 (23rd November 2016) - Burgess, Michael; Leung, Matthew; Chellapah, Anthony; Clark, Jonathan R.; Batstone, Martin D.
Abstract: Background: Significant oral function is often lost after surgical therapy for head and neck cancer. The use of osseointegrated implants for reconstruction in patients with head and neck surgery has shown to significantly improve the quality of life for these patients. Variable success rates range from 99% to 70%. Methods: A retrospective audit of patient records was performed looking at cumulative survival of implants. Inclusion criteria were patients who were treated at 1 of 2 designated Australian Head and Neck Units and received oral osseointegrated implants. Results: Fifty‐nine patients were included for analysis. One hundred ninety‐nine implants were placed into vascularized bone grafts (VBGs). There were 11 implant failures with an overall success rate of 94.5%. There was 1 significant adverse outcome with a pathological fracture of a flap after implant placement. Implant success in scapula and iliac crest flaps was comparable to fibula flaps. Conclusion: Implants placed into VBGs have a reasonable success rate in well‐selected patients. © 2016 Wiley Periodicals, Inc. Head Neck 39: 443–447, 2017